Single Versus Double Dose Praziquantel Comparison on Efficacy and Schistosoma mansoni Re-Infection in Preschool-Age Children in Uganda: A Randomized Controlled Trial. - Allen Nalugwa; Fred Nuwaha; Edridah Muheki Tukahebwa; Annette Olsen (Public Library of Science (PLoS), 2015)
BACKGROUND:Schistosoma mansoni infection is proven to be a major health problem of preschool-age children in sub-Saharan Africa, yet this age category is not part of the schistosomiasis control program. The objective of this study was to compare the impact of single and double dose praziquantel (PZQ) treatment on cure rates (CRs), egg reduction rates (ERRs) and re-infection rates 8 months later, in children aged 1-5 years living along Lake Victoria, Uganda. METHODOLOGY/PRINCIPAL FINDINGS:Infected children (n= 1017) were randomized to receive either a single or double dose of PZQ. Initially all children were treated with a single standard oral dose 40 mg/kg body weight of PZQ. Two weeks later a second dose was administered to children in the double dose treatment arm. Side effects were monitored at 30 minutes to 24 hours after each treatment. Efficacy in terms of CRs and ERRs for the two treatments was assessed and compared 1 month after the second treatment. Re-infection with S. mansoni was assessed in the same children 8 months following the second treatment. CRs were non-significantly higher in children treated with two 40 mg/kg PZQ doses (85.5%; 290/339) compared to a single dose (83.2%; 297/357). ERRs were significantly higher in the double dose with 99.3 (95%CI: 99.2-99.5) compared with 98.9 (95%CI: 98.7-99.1) using a single dose, (P = 0.01). Side effects occurred more frequently during the first round of drug administration and were mild and short-lived; these included vomiting, abdominal pain and bloody diarrhea. Overall re-infection rate 8 months post treatment was 44.5%. CONCLUSIONS:PZQ is efficacious and relatively safe to use in preschool-age children but there is still an unmet need to improve its formulation to suit small children. Two PZQ doses lead to significant reduction in egg excretion compared to a single dose. Re-infection rates with S. mansoni 8 months post treatment is the same among children irrespective of the treatment regimen.